Too complicated for the field?: measuring quality of care in humanitarian aid settings - Kersten, Roland; Bosse, Götz; Dörner, Frank; Slavuckij, Andrej; Fernandez, Gustavo; Marx, Michael (Global health action, 2013)
While quality of care is a major concern in the western world, not many studies investigate this topic in low-income countries. Even less is known about the quality of care in humanitarian aid settings, where additional challenges from natural or manmade disasters contribute to additional challenges. This study tried to address this gap by introducing a new approach to systematically measure quality of care in a project of Médecins Sans Frontières (MSF) in Agok area, between South Sudan and Sudan. Our objective was to obtain a valid snapshot of quality of care for a MSF project in three weeks that has the potential to serve as a baseline for quality improvement strategies. The evaluation followed a cross-sectional study design to assess structural, process and outcome quality according to Donabedian's criteria of quality of care. A bundle of well-established methods for collection of quantitative and qualitative data was used to assess the project by following a triangulated mixed-methods approach. Mean structural quality scored 73% of expected performance level and mean process quality 59%. The overall mortality rate for the hospital was 3.6%. On average, less complicated cases got a better level of care than patients who were seriously ill. Significant motivational issues were discovered in staff interviews potentially affecting quality of care. The tool appeared to be quick, feasible and effective in judging quality of care in the selected project. To tap the whole potential of the approach a re-evaluation should be carried out to assess the effectiveness of implemented improvement strategies in Agok. To confirm the usefulness of the approach, more studies are needed covering the variety of different humanitarian aid settings.
Gesehen am 28.04.2021